A study on the room-temperature magnetoplastic effect of silicon and its mechanism. (17th August 2021) - Zhang, Xu; Zhao, Qian; Wang, Zheyao; Cai, Zhipeng; Pan, Jiluan
Abstract: Exposure to a magnetic field at room temperature was found able to promote the dislocation motion and distortion relaxation in silicon. The Kernel average misorientation maps of the silicon samples obtained by electron backscatter diffraction (EBSD) showed that a magnetic field ∼1 T can cause dislocation movement of hundreds of nanometers. And the EBSD image quality maps indicated that the magnetic field can cause the relaxation of the lattice distortion. The Δ g mechanism of the magnetically stimulated changes was discussed.